(untitled) (Docentes 2.0 Journal, 2020)
In this investigation, I analyzed the benefits offered by a virtual classroom in the learning of the students of the general baccalaureate. For the data collection, surveys and interviews were used, for which I conducted an interview with the directors of the school, surveyed 10 teachers, in addition to 112 students, resulting in an improvement in learning. This research proposes to analyze the impact of the virtual classroom in the learning process in the students of the general baccalaureate, for the design of the virtual learning environment based on the Moodle platform. Analyzing the results, it is established that, the student must make use of the virtual classroom to acquire new knowledge to increase their academic performance, because this technological tool helps to perform autonomous works sent by teachers to complement daily tasks. We use the Moodle platform for the design of the virtual classroom, which allows: Distribute information, exchange ideas, experiences, apply, experience what has been learned, evaluate knowledge, and maintain both security and reliability in the System. It is also concluded that using the virtual classroom the student can build their own knowledge based on previous knowledge, thanks to the simple use of technology and computer applications.